Ethical Aspects of Brain Organoid Research in News Reports: An Exploratory Descriptive Analysis - Ide, Kazuki (Medicina (Kaunas), 2021)
Background and Objectives: Brain organoids are self-assembled, three-dimensional (3D) aggregates generated from pluripotent stem cells. These models are useful for experimental studies on human brain development and function and are therefore increasingly used for research worldwide. As their increasing use raises several ethical questions, we aimed to assess the current state of the press on brain organoid research using a cross-sectional database to understand the extent of discussion of this subject in the public. Materials and Methods: We conducted a descriptive analysis of news reports obtained from the Nexis Uni database, searched in April 2020. After extracting the news reports, the number of published reports in each year and the included terms were analyzed. Results: Up to April 2020, 332 news reports had been published, with over half of them published in the United States and the United Kingdom, with the numbers gradually increasing every year. In total, 113 (34.0%) news reports included ethics-related keywords, and the ratio of studies before and after the study-period midpoint was significantly increased (21.0% (2013–2016) vs. 38.2% (2017–2020); p = 0.0066, Chi-square test with Yates’ continuity correction). Conclusions: Although news reports on the ethical aspects of brain organoid research have been increasing gradually, there was a bias in the region of publication. Additional studies focusing on the ethical aspects of brain organoid research should strive to assess the public perception on the subject in different parts of the world.